Ambaeolothrips: a new genus of Neotropical Aeolothripidae (Thysanoptera), with observations on the type-species from mango trees in Mexico - Mound, Laurence; Cavalleri, Adriano; O’donnell, Cheryle; Infante, Francisco; Ortiz, Antonio; Goldarazena, Arturo (Zootaxa, 2016)
Ambaeolothrips gen. n. is diagnosed for three Neotropical species: the type species romanruizi Ruiz-De la Cruz et al. comb. n. from Mexico, microstriatus Hood comb. n. from Panama, and pampeanus sp. n. from southern Brazil. Variation is discussed among character states that are used in the generic classification of the family Aeolothripidae, including segmentation of the antennae and maxillary palps, sculpture of the metanotum and presence of sternal discal setae. New field observations on the biology of romanruizi indicate that this species is phytophagous in flowers and on leaves, with no evidence of predation on the larvae of other thrips.